Commas say "take a break" - Dahl, Michael; Garbutt, Chris (2019)
"Commas love taking breaks. In fact, they want everyone to take breaks! Follow along and learn all about commas"--
Ages 6-8.
Keywords: Comma -- Juvenile literature; English language -- Punctuation -- Juvenile literature; English language -- Punctuation